The impact of platform corporate venture capital vs. traditional corporate venture capital on internet initial public offering underpricing: Evidence from Chinese-listed internet firms - Fu, Feng; Chen, Shuangying (Frontiers in Psychology, 2022)
Purpose –Platform firms are playing an increasingly major role in venture investment. Based on the motivation perspective and signaling theory, this paper examines the effects of platform corporate venture capital (CVC) versus traditional CVC on Internet IPO underpricing. Design/methodology/approach –The sample consists of 117 Chinese Internet firms that went public between 2004 and 2019. Two-stage Heckman regression analysis was used to test several hypotheses. Findings –This paper finds that , compared to traditional CVC firms, platform CVC firms increase Internet IPO underpricing. In particular, with the contingency of strong prior performance or implementation of China’s “Internet plus” policy, platform CVC firms increase Internet IPO underpricing more than traditional CVC firms. With increasing Internet penetration, platform CVC firms will increase Internet IPO underpricing less than traditional CVC firms. Practical implications – As CVC firms differ in their key resources and motivations used to realize their strategic goals, IPO firms should formulate their resource acquisition strategies according to their resource needs and the contexts in which they operate. Originality/value –By identifying the differences between platform CVC and traditional CVC, this paper complements previous research on the role of CVC backing of IPOs, and extends the knowledge of CVC investment by shedding light on the contingency value of corporate investors and Internet IPO underpricing in emerging markets.